Expression of peanut agglutinin-binding mucin-type glycoprotein in human esophageal squamous cell carcinoma as a marker - Balakrishnan Ramathilakam; S Chandramohan; VV Taralakshmi; Steven Arulraj H; Jayakumar Kamala; Niranjali Devaraj; Lakku Reddi A; Kannan Sankaranarayanan; Schmidt Christian; Halagowder Devaraj (Molecular Cancer, 2003)
Abstract Background The TF (Thomson – Friedenreich) blood group antigen behaves as an onco-foetal carcinoma-associated antigen, showing increased expression in malignancies and its detection and quantification can be used in serologic diagnosis mainly in adenocarcinomas. This study was undertaken to analyze the sera and tissue level detectable mucin-type glycoprotein (TF-antigen) by Peanut agglutinin (PNA) and its diagnostic index in serum as well tissues of human esophageal squamous cell carcinoma as marker. Results We examined 100 patients for serological analysis by Enzyme Linked Lectin Assay (ELISA) and demonstrated a sensitivity of 87.5%, specificity of 90% and a positive predictive value of 95%. The immuno-histochemical localization of TF antigen by Fluorescence Antigen Technique (FAT) in 25 specimens of normal esophageal squamous epithelium specimens and 92 specimens with different grades of, allowed a quicker and more precise identification of its increased expression and this did not correlate with gender and tumor size. There was a positive correlation between membrane bound TF antigen expression with different histological progression, from well differentiated to poorly differentiated, determined by PNA binding. Specimens showed morphological changes and a pronounced increase in PNA binding in Golgi apparatus, secretory granules of the cytosol of well differentiated and an increased cell membrane labeling in moderately and poorly differentiated, when compared with ESCC and normal tissues. Conclusion The authors propose that the expression of TF-antigen in human may play an important role during tumorigenesis establishing it as a chemically well-defined carcinoma-associated antigen. Identification of the circulating TF-antigen as a reactive form and as a cryptic form in the healthy individuals, using PNA-ELLA and Immunohistochemical analysis of TF antigen by FAT is positively correlated with the different histological grades as a simple and cost-effective method for the early diagnosis of ESCC. The present study reveals that, during tumorigenesis, an aberrant glycosylation takes place in Golgi apparatus leading to over secretion of TF antigen into the cytoplasm along with mucin granules and later into cell membrane. We suggest that the further characterization of TF antigen may unravel pathogenetic aspects of this silent disease.